New Tanytarsus van der Wulp from the Brazilian Amazonia indicate clues to intrageneric relations (Diptera: Chironomidae) - Dantas, Galileu P.s.; Giłka, Wojciech (Zootaxa, 2017)
Three new distinctive species of the genus Tanytarsus van der Wulp, 1874 are described from the Amazon rainforest, Brazil, and their systematic position is analysed. As a result, three new species groups are proposed. Tanytarsus illustris sp. nov. (Roraima) couples with T. hirsutus Trivinho-Strixino, Wiedenbrug et da Silva, 2015, both species featuring an elongated hypopygial anal tergite point lacking crests and spinulae, a strongly shortened digitus and a median volsella bearing two peculiar lamellae (the Tanytarsus hirsutus species group). Tanytarsus insignis sp. nov. (Amazonas) keys with T. impar Trivinho-Strixino et Strixino, 2004 and T. magnus Trivinho-Strixino et Strixino, 2004, all the species distinct in having an elongate superior volsella and digitus, a strong club-shaped inferior volsella and anal point lacking crests and/or spinulae (the Tanytarsus impar species group). Tanytarsus insolens sp. nov. (Amazonas) displays an extraordinarily structured, bilobed superior volsella, the character treated as diagnostic for a group proposed for this species and T. kiche Vinogradova, Riss et Spies, 2009 (the Tanytarsus kiche species group).